DEVELOPMENT OF EDUCATIONAL CASES ON OBSERVING THE REQUIREMENTS OF LABOR PROTECTION IN PRODUCTION (Innovative professional education, 2024)
The article offers examples of the development of educational cases in the process of training future skilled workers. The introduction of educational cases into the educational process will contribute to the assimilation of modern European labor safety standards, will form a healthy environment for Ukrainian business of all forms of ownership.
Keywords: educational cases, education seekers, future skilled workers, labor protection